Thirdspace politics: A study of the dialectics of space production in settlements along the Dupak Magersari railway line - Galang Geraldy (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2026)
Informal settlements along railway lines are generally understood as a consequence of urbanisation, poverty, or weak enforcement of spatial planning regulations. This article seeks to explain how the space along the Dupak Magersari railway line in Surabaya is produced through the dialectical relationship between the community’s spatial practices, the state’s representation of space, and the residents’ collective lived experiences. The research employs a qualitative approach using a case study design. The analysis draws on Henri Lefebvre’s perspective on the production of space and Edward Soja’s concept of ‘Thirdspace’. The findings reveal that the railway corridor area developed through the occupation of space driven by the need for access to livelihoods around Pasar Turi and the economic networks of North Surabaya. Over time, these spatial practices have resulted in socio-spatial consolidation that shapes community identity, collective capacity and various local institutions. On the other hand, the state reproduces space through railway regulations, population administration and fiscal instruments that are not entirely aligned with one another. This fragmentation of the conceived space opens up scope for ongoing negotiation between residents, the government, PT KAI, civil society organisations and academic groups. This study concludes that Dupak Magersari represents a ‘Thirdspace’, namely a hybrid space produced through the co-production of space and socio-spatial negotiation within the context of a post-colonial city.